Assessment of Nutritional, Functional, and Sensory Characteristics of Bread Produced with Wheat, Cowpea Bran, and Prekese (Tetrapleura tetraptera) Flour Composites - Orafa P. N; Grace Ezekiel; Taiwo Mayomi Adenike; Tar Sesugh Solomon (Kwaghe International Journal of Sciences and Technology, 2026)
Incorporating legume bran and indigenous functional ingredients into wheat-based bread offers a pathway to improve nutritional quality, but their effects on product characteristics require empirical evaluation. This study evaluates the nutritional, functional, mineral, physical, and sensory properties of bread produced from wheat, cowpea bran, and prekese flour blends. Cowpea bran was cleaned, soaked to rehydrate, dried, milled, and sieved prior to blending, and wheat–cowpea bran–prekese formulations were prepared at ratios of 100:0:0, 95:5:5, 90:10:5, 85:15:5, and 80:20:0. Proximate, functional, mineral, physical, and sensory characteristics were determined using standard analytical methods. Proximate analysis showed significant differences (p < 0.05), with moisture, ash, fat, fiber, protein, and carbohydrate contents ranging from 5.26–10.13%, 1.75–3.03%, 8.08–8.70%, 0.14–6.71%, 9.12–12.22%, and 75.72–59.85%, respectively. Functional properties—bulk density, swelling capacity, water absorption, oil absorption, and foaming capacity—varied from 0.62–0.73, 3.31–4.21, 2.06–2.81, 1.25–1.40, and 5.30–12.51, while mineral contents of calcium, iron, zinc, and potassium ranged from 335.34–375.28, 16.63–52.58, 6.57–54.06, and 485.14–505.13, respectively. Sensory scores for appearance, flavor, color, mouthfeel, and overall acceptability ranged from 5.35–8.55, 5.33–7.83, 5.45–8.34, 4.75–8.38, and 4.45–8.58, with the 100% wheat formulation showing the highest overall acceptability, while the 80:20:5 blend was the least preferred due to its higher cowpea bran content despite improved nutritional attributes. Overall, the findings highlight the potential of cowpea bran and prekese flour as functional ingredients for enhancing the nutritional profile of wheat-based bread, while underscoring the need for optimal formulation strategies to balance nutritional benefits with desirable sensory and functional properties for consumer acceptance and product development.